The use of borax pentahydrate of ınorganıc fıller ın medıum densıty fıberboard productıon - Çamlıbel, Osman; Akgül, Mehmet (Maderas. Ciencia y Tecnología, 2020)
The aim of the study was the use of the inorganic borax pentahydrate mineral in medium density fiberboard production instead of biomass fiber and to specify the performance which physical, mechanical, combustion of produced boards. Chips used in manufacture were subjected to cooking for 4,5 minutes in Asplund defibrator at the vapor pressure of 7,6 kg/cm2 pressure and 190 ºC temperature. 1,6 % paraffin according to based on oven-dried wood fibers was added to cooked chips before the fiber processing in segments of defibrillator section. 1 % ammonium sulphate according to based on oven-dried wood fibers were added to fiber in the bowline. Borax pentahydrate was prepared in a separate tank in order to use the production of medium density fiberboard medium density fiberboard. Borax pentahydrate inorganic mineral was mixed with urea-formaldehyde resin. Urea-formaldehyde glue was prepared as three different solutions including the borax pentahydrate as 3 % (20 kg), 6 % (40 kg) and 9 % (60 kg) respectively. Borax pentahydrate mixed fibers were dried to 12 % moisture. Mat was formed before prepress. Daily multi-press was manufactured 188 °C temperature and 32 kg/cm² pressure and 270 second pressing time. Manufactured boards size were 2100x4900x18 (mm). According to this work result, 3 % and 6 % rate borax pentahydrate added medium density fiberboard boards were measured more good physical and mechanical test results compare to control boards. 9 % borax pentahydrate added medium density fiberboard boards were shown incredibly superior performance at fire resistance.